Cocultivation Study of Monascus spp. and Aspergillus niger Inspired From Black-Skin-Red-Koji by a Double-Sided Petri Dish - Yuan, Xi; Chen, Fusheng (Frontiers in Microbiology, 2021)
The cocultivation is an emerging and potential way to for various uses. Extensive researches have been carried out over the years but some cocultivation modes are not easy to implement in laboratory, especially the fungus-fungus (FF) mode, owing to the reasons such as different growth rate, limited growth space, hyphae intertwining, and difficulty in sample separation, etc. In this research, a double-sided petri dish (DSPD) was designed and carried out as a tool to study FF cocultivation in laboratory. In this research, a natural FF mode, Monascus spp. and Aspergillus niger inspired from Black-skin-red-koji, was studied. By using DSPD, the obstacles in FF cocultivation study were overcome such as growth space problem, hyphae intertwining problem and mycelium separation by co-culturing M. spp. and A. niger on each side of DSPD. Monocultured and co-cultured M. spp. and A. niger were compared and analyzed, including colony morphology, micromorphology, and main secondary metabolites of M. spp. analyzed by High Performance Liquid Chromatography (HPLC). A novel substance was found to be produced by M. ruber M7 when co-cultured with A. niger CBS 513.88. Also, the primary obstacle, sample preparation and separation, has been overcome. Thereafter the transcriptome data of good quality for further analysis was obtained. Therefore, DSPD might be an efficient tool for theoretical fundaments-related studies of cocultivation.